Iluzja wiedzy w zakresie wsp?łczynnik?w niezawodności metakognitywnego monitoringu działań edukacyjnych student?w = The illusion of knowing from perspective of metacognitive monitoring accuracy of educational activity of university students - Pasičnik, Igor D.; Kalamaž, Ruslana V.; Avgustuk, Maria M. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study analyses the results of the empirically established connections between the features of the singled out personal, cognitive and metacognitive characteristics of students. In particular, it is established that the illusion of knowing regarded as an overconfidence and an error of metacognitive monitoring occurs in all types of metacognitive judgments, but is more evident in prospective judgments.
Keywords: iluzja wiedzy; metakognitywny monitoring; działalność edukacyjna; wiekowe cechy i odmienności płciowe; illusion of knowing; metacognitive monitoring; educational activity; overconfidence; underconfidence